Objective Measurement and Characterization of Sleep Benefit in Parkinson's Disease. Issue 4 (25th May 2017) - Lee, Will; Evans, Andrew H.; Williams, David R.
Abstract: Background: Sleep benefit (SB) in Parkinson's disease refers to improved motor symptoms upon waking despite an entire night without medications. Although it was first proposed 30 years ago, this phenomenon proved difficult to investigate, and its true prevalence and underlying mechanisms remain unclear. Objective: This study aimed to identify and quantify SB through measurement of motor function using a validated smartphone application and to identify disease characteristics that predicted SB. Methods: Ninety‐two patients recruited from 2 Movement Disorder Services were clinically assessed at home using a validated smartphone application. Each patient was tested in the on‐state, at the end of dose, and on waking (before medications) 3 times. Differences between the 3 states were used to determine the impact of sleep and levodopa on motor function. SB was considered to be a "measurable improvement in parkinsonism from the end of dose." Results: The morning waking motor function of 20 patients (22%) improved compared with the end‐of‐dose function, with 9 patients demonstrating superior function compared with their on‐state. No clinical features predicted SB. Although all participants subjectively reported motor fluctuations, only 35 patients (38%) demonstrated an objective improvement with levodopa. Patients who had SB more often demonstrated objective motor fluctuations compared with those who did not (65% vs. 31%; P = 0.008). Conclusions: SB is a genuine motor phenomenon: 1 in 5 patients have a measurable improvement in motor function on waking. It remains questionable whether this improvement is a direct effect of sleep. Until its underlying mechanism is better understood, it is more appropriate to refer to this phenomenon as simply morning improvement or diurnal fluctuation of motor symptoms.